Telaah Tafsir Marah Labid Karya Nawawi al-Bantani - Anas Mujahiddin; Muhammad Asror (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2021)
Marah Labid is one of Tafsir which written by Nusantara Mufassir. Many boarding schools study about this tafsir. Nawawi al-Bantani wrote this book after seeing and interacting with his community directly. This research will expose how Nawawi al-Bantani has written this book. This research conducted the library research which did not only focus in studying Marah Labid but also the comments of others about this book. The result of this research is that Nawawi al-Bantani used Tahlili Method in interpreting al-Qur’an.